2021
DOI: 10.18502/cmm.7.1.6181
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antifungal drug resistance of nosocomial Candida species isolated from two university hospitals in Egypt

Abstract: Background and Purpose: There is a significant rise in morbidity and mortality of infections caused by Candida. Candida spp. infections are currently ranked fourth among nosocomial infections which are difficult to diagnose and refractory to therapy.Given the differences in susceptibility among various spp., identification of Candida spp. is an important step that leads to the selection of a suitable antifungal. Materials and Methods: A prevalence study was on 122 Candida isolates. The Candida spp. were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…However, our finding contradicted the earlier report of El-Ganiny et al, 18 from Egypt who stated that C. albicans was the main prevalent spp. (57.4%).…”
Section: Discussioncontrasting
confidence: 99%
“…However, our finding contradicted the earlier report of El-Ganiny et al, 18 from Egypt who stated that C. albicans was the main prevalent spp. (57.4%).…”
Section: Discussioncontrasting
confidence: 99%
“…Among the isolated NAC, C. parapsilolsis (17.3%) and C. glabrata (13.5%) represented the majority of spp. Our results were consistent with a previous study from Egypt that reported high prevalence rates of C. albicans among ICU patients followed by NAC 32 . In addition, a former study conducted in Iran has reported that C. albicans was the commonest cause of Candida infection (62.4%), followed by C. parapsilolsis (17.5%) and C. glabrata (8.8%) 25 .…”
Section: Discussionsupporting
confidence: 93%
“…It is widely accepted that Candida develops rapidly resistance to azoles and echinocandins. Nevertheless, resistance to amphotericin B remains extremely rare mostly because the fitness cost of developing modifications for survival is high 25 .In our study, the in vitro sensitivity testing of C. albicans isolates, isolated from systemic candidiasis revealed that the antifungal with the greatest sensitivity was nystatin (88%) followed by ketoconazole and amphotericin B (76%, 72%) respectively, fluconazole and itraconazole susceptibility rates were (60%). Similarly, Khairat et al 26 showed 94.4% sensitivity to nystatin.…”
Section: Discussionmentioning
confidence: 65%